Poverty Alleviation and Interhousehold Transfers : Evidence from BRAC's Graduation Program in Bangladesh - Gulesci, Selim (World Bank, Washington, DC, 2020)
Poor households often rely on transfers from their social networks for consumption smoothing, yet there is limited evidence on how antipoverty programs affect informal transfers. This paper exploits the randomized roll-out of BRAC's ultra-poor graduation program in Bangladesh and panel data covering over 21,000 households over seven years to study the program's effects on interhousehold transfers. The program crowds out informal transfers received by the program's beneficiaries, but this is driven mainly by outside-village transfers. Treated ultra-poor households become more likely to both give and receive transfers to/from wealthier households within their communities; and less likely to receive transfers from their employers. As a result, the reciprocity of their within-village transfers increases. The findings imply that, within rural communities, there is positive assortative matching by socio-economic status. A reduction in poverty enables households to engage more in reciprocal transfer arrangements and lowers the interlinkage of their labor with informal insurance.